Test Appraisal System Application Based on YII Framework as Media Input Student Value Final Project and Thesis Session at Higher Education - Zarlis, Muhammad; Harahap, Eka Purnama; Husna, Lina Naelal (Pandawan, 2019)
System development is a form of effort to improve the quality of the system to be more innovative. Raharja College is a college of computer science that has many systems to support its academic activities. At Raharja College there is a Thesis Session Assessment and Final Assignment system which makes it easy for lecturers as a media to provide a thesis trial or final assignment assessment. The Testing Assessment System is very important in the process of running a thesis trial or final assignment, because it makes it easier for lecturers to provide an assessment of the results of student thesis research. However, in the current assessment system, the testers have problems, which are still using local networks, which of course still use UTP cables as their connector. by online. In the development of the scoring system these testers use the method of swot analysis and elicitation. And use one of the PHP Framework, Yii Framework.